THE RELATIONSHIP BETWEEN BANK LOANS and ECONOMIC GROWTH in TURKEY: 1995-2010 - Zortuk, Mahmut; Çelik, M.Yunus (ummary (just) of this article presented the III. International Symposium of Sustainable Development, Sarajevo, 2012)
In this study, we aim to determine the direction of the relationship between the economic growth and total credits of Turkish Banks. In our study, we analyzed this relationship for the period 1995-2010, by using quarterly data analysis. In the analyses, change in the volume of real credits is used to represent the variable, total credits; and real growth in GDP represents the variable, growth. This study uses Unit Root Test and Todo-Yamamoto Causality Analysis as econometric methods. As a result of the analysis and evaluations, it is found that from the growth to the credits there has been a uni-directional causality relation.
Keywords: Bank Loan (BL), Economic Growth (EG), Ziwot Andrews Breakpoint test (ZABT), Todo-Yamamoto test (TYT).